THE LEGACY OF KHALEL ARGYNBAYEV ON KAZAKH FAMILY RITUALS (Journal of history, 2024)
In connection with the celebration in 2024 of the 100th anniversary of the birth of a major ethnographer, one of the founders of Kazakh ethnography, Kh.A. Argynbaev, the Ch.Ch. Valikhanov Institute of History and Ethnology began implementing a grant project for the purpose of academic reprinting in Kazakh and Russian languages ​​of the scientist’s works, thereby making them available to a wider circle of professional scientists, as well as the general public to popularize knowledge on the historical ethnography of the Kazakhs among a wide Russian-speaking audience. The purpose of this article is to highlight the contribution of Kh. Argynbaev to the study of Kazakh wedding rituals, which had several successive stages. The research methodology is based on general scientific methods of logical analysis and synthesis, a structural-functional approach, in which family rituals as a social institution are considered part of the rituals of the family cycle, and internally are divided into a series of sequential rituals, for example, preliminary wedding negotiations, matchmaking, etc. The factual material, conclusions and assessments of the study can be used in the scientific and educational process, when conducting lectures and practical classes with students in major specialties at all levels of training (bachelor's, master's and doctoral studies), when compiling educational and methodological complexes of elective disciplines, writing textbooks and textbooks on the ethnology of Kazakhstan, the history of science.
Keywords: historical and cultural heritage; bride price; wedding rituals; matchmaking; seeing off the bride; wedding